Efficacy of prophylactic antiviral therapy and outcomes in HBsAg-negative, anti-HBc-positive patients receiving chemotherapy: a real-life experience. Issue 1 (January 2017) - Papadopoulos, Nikolaos; Deutsch, Melanie; Manolakopoulos, Spilios; Bitsi, Chrysoula; Michalakeas, Helias; Poulakidas, Helias; Tsironi, Eftychia; Giannouli, Stavroula; Papatheodoridis, George V.; Koskinas, John; Pectasides, Dimitrios
Abstract : Objective: The aim of this study is to evaluate the outcomes of hepatitis B surface antigen (HBsAg)-negative, anti-HBc-positive patients who received immunosuppressive therapies. Patients and methods: We retrospectively evaluated the medical records of HBsAg-negative, anti-HBc-positive patients with hematological diseases or solid tumors who underwent immunosuppressive therapies and were referred because of positive baseline hepatitis B virus (HBV) serology or HBV reactivation. The referral date was according to the judgment of the treating physician at the time of identification of any signs of HBV infection. Results: We included 55 HBsAg-negative, anti-HBc-positive patients. Of these, 31 received antiviral prophylaxis (group 1), whereas 24 patients did not receive any anti-HBV agent (group 2). The majority of patients [49/55 (89%)] had hematological malignancies and most of them 39/55 (71%) received rituximab-containing regimens. Lamivudine was used as antiviral prophylaxis in 13/31 (42%) patients of group 1. One patient in this group experienced HBV reactivation and was treated successfully with tenofovir add-on therapy. All patients in the second group experienced HBV reactivation and most of them [19/24 (79%)] were treated with tenofovir or entecavir as rescue therapy. Two of these patients (one of the tenofovir/entecavir subgroup and one of the lamivudine subgroup) eventually died because of hepatic failure despite rescue treatment. Conclusion: Patients with serological markers of previous HBV infection are still at risk for HBV reactivation. Screening of both anti-HBs and anti-HBc is mandatory before chemotherapy. Pre-emptive antiviral prophylaxis, including lamivudine, is highly effective in all subgroups of such patients, whereas deferring treatment upon HBV reactivation is not enough to rescue all cases.